Experimental investigation of the reliability of Printed Circuit Board (PCB)-embedded power dies with pressed contact made of metal foam. (September 2018) - Pascal, Y.; Labrousse, D.; Petit, M.; Lefebvre, S.; Costa, F.
Abstract: A Printed Circuit Board (PCB)-embedding process using pressed metal foam to connect the top-side pads of power dies is considered. The manufacturing process, simple and highly cost-effective, is described in detail; samples are manufactured and their reliability and robustness are characterised. It is shown that thermally cycled prototypes exhibit reliability close to that of Direct Bounded Copper (DBC) substrates. Samples submitted to 150 A-surges have highly scattered reliability. SiC MOSFETs submitted to destructive current limiting tests and repetitive short-circuit tests performed similarly to dies reported in TO247 packages. A discussion on the development of reliability-assessment-methods, especially suited for PCB-embedding processes, is proposed. Highlights: Robustness and reliability of a pressed contact made of metal foam is investigated. Some aged samples perform as well as DBC and wire-bonded chips. Short-circuit robustness and reliability are similar to that of wire-bonded dies. Repeatability is still under investigation. New reliability-assessment-methods suited to PCB-embedding processes must be defined.